- PENGARUH EDUKASI GAGAL GINJAL KRONIS TERHADAP POLA NUTRISI DAN STATUS KESEHATAN PASIEN HEMODIALISA: SEBUAH STUDI PRE EKSPERIMENTAL: - - MUHAMMAD ARIF BASTOMI NASAH HUDIN; Dodik Hartono; Alwin Widhiyanto (Institut Teknologi, Sains, dan Kesehatan RS.DR. Soepraoen Kesdam V/BRW, 2024)
Chronic Kidney Disease (CKD) occur in the majority of adults in the world (11-13%). CKD ranks as the 10th class of non-communicable diseases. The prevalence of CKD in Indonesia is the highest age ≥ 15 years, in 2013 (0.2%), in 2018 (0.38%), in 2019 in the group of 45-64 years (30.45%). in East Java Province (4,828) new cases. The preliminary study on 10 patients, 6 patients (60%) said they did not understand CKD, dietary, maintain health status, while 4 patients (40%) knew CKD but did not understand dietary patterns, maintain health status. The purpose to analysis effect of CKD education on nutritional patterns, health status of hemodialysis patients. Methods Pre experimental one group pretest-postest. The population all hemodialysis patients in June-August 2022 werw 40 people, sample 20 people, consecutive sampling, education sheet, instruments, leaflets, questionnaires, Wilcoxon. The results 41-60 y.o (55.0%), male (60.0%), high school education (55.0%), 35.0% entrepreneurship, nutrition patterns before intervention were not good (40.0%), after it were quite good (65.0%), health status before it was quite good (90.0%), after it was good (55.0%); p values of nutritional patterns; health status (p1=0.000; p2=0.003 <α 0.05). Conclusion is an influence of CKD education on nutritional patterns and health status.